Pendampingan Pemanfaatan E-Commerce Teknologi Digital Terhadap Pendapatan Pemilik UMKM Di Desa Medan Krio - Adinda Syafira; Sani Susanti (Pusmedia Group Indonesia, 2026)
This study aims to determine the utilization level of digital technology-based e-commerce among MSME owners in Medan Krio Village, analyze their income levels, and examine the effect of e-commerce utilization on business revenue. This research employed a quantitative approach with an associative method. The research population comprised all MSME owners in Medan Krio Village, with a sample of 53 respondents selected via a purposive sampling technique based on specific criteria, namely businesses that have adopted digital platforms. The results indicated that the utilization of digital technology-based e-commerce among MSME owners in Medan Krio Village fell into the high category. Nevertheless, its implementation was not yet optimal in several technical aspects, such as online transaction management and platform optimization to boost sales volume. Meanwhile, the income level of the MSME owners was classified into the moderate category, as most respondents had not fully experienced a significant surge in revenue after adopting e-commerce. The simple linear regression analysis generated the equation Y = 42,847 + 0,467X, indicating that every one-unit increase in e-commerce utilization will increase MSME revenue by 0.467 units. Furthermore, the t-test yielded a tstatistic value of 4.794 with a significance value of 0,000 < 0,05, proving that the utilization of digital technology-based e-commerce has a positive and significant effect on the income of MSME owners in Medan Krio Village. In addition, the coefficient of determination test showed an R Square value of 0.311, implying that e-commerce utilization accounts for 31,1% of the variance in MSME revenue, while the remaining 68,9%is influenced by other factors outside the scope of this study. The implication of this research reinforces the theory that digital technology utilization is a crucial factor in enhancing business performance, demonstrating that e-commerce optimization will yield a tangible impact when fully integrated into marketing, transactions, and customer communication.